Anxiety and depression scores in maternity healthcare workers during the Covid‐19 pandemic. Issue 2 (25th August 2020) - Corbett, Gillian A.; Milne, Sarah J.; Mohan, Suruchi; Reagu, Shuja; Farrell, Tom; Lindow, Stephen W.; Hehir, Mark P.; O'Connell, Michael P.
Abstract : Healthcare workers are at significant risk of psychological morbidity during the COVID‐19 pandemic. Anxiety and depression is highest in young, female, and supportive workers.